1999
DOI: 10.1074/jbc.274.49.35240
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene Activates the Human p53 Gene through Induction of Nuclear Factor κB Activity

Abstract: p53 is known to be recruited in response to DNAdamaging genotoxic stress and plays an important role in maintaining the integrity of the genome. In the present study, the effect of a potent lung cancer carcinogen, benzo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 40 publications
6
44
1
2
Order By: Relevance
“…For this purpose, plucp53NFkBmut was constructed from pluc-mp53 recombinant by inactivating the p53-promoter NF-kB site. In agreement with already published data (Pei et al, 1999), inactivation of NF-kB site signi®cantly diminishes the level in the luciferase gene expression from the p53-promoter (Figure 6d, control). Furthermore, the co-expression of IkBa inhibits the luciferase expression from pluc-mp53 but not from plucp53NFkBmut (Figure 6d,+IkBa).…”
Section: Overexpression Of Mnsod Inhibits P53-dependent Apoptosissupporting
confidence: 80%
See 1 more Smart Citation
“…For this purpose, plucp53NFkBmut was constructed from pluc-mp53 recombinant by inactivating the p53-promoter NF-kB site. In agreement with already published data (Pei et al, 1999), inactivation of NF-kB site signi®cantly diminishes the level in the luciferase gene expression from the p53-promoter (Figure 6d, control). Furthermore, the co-expression of IkBa inhibits the luciferase expression from pluc-mp53 but not from plucp53NFkBmut (Figure 6d,+IkBa).…”
Section: Overexpression Of Mnsod Inhibits P53-dependent Apoptosissupporting
confidence: 80%
“…Considering the fact that MnSOD has been shown to modulate NF-kB activity (Li et al, 1998), and that NF-kB regulates p53 promoter activity (Wu and Lozano, 1994;Hellin et al, 1998;Pei et al, 1999), we were led to analyse the eect of an overexpression of MnSOD on p53 promoter activity. We then cotransfected pluc-mp53, a plasmid encoding the luciferase reporter gene under the control of the mouse p53 promoter, with increasing amounts of MnSOD expression vector, in H1299 cells.…”
Section: Overexpression Of Mnsod Inhibits P53-dependent Apoptosismentioning
confidence: 99%
“…In this line of evidence, it was previously reported that p53 gene expression is activated through NF-kB after Benzo(a)pyrene treatment. 15 The idea that p53 accumulation results from a higher transcription rate rather than from the protein stabilization is emphasised by the fact that TNFa did not induce p53 phosphorylation at Ser-20. Indeed, phosphorylation at Ser-20 has been shown to inhibit p53 interaction with the ubiquitin-ligase MDM2, preventing p53 degradation by the proteasome pathway and thereby promoting p53 stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NF-kB also regulates the expression of the tumour suppressor gene p53, 13 although the role of this regulation is not well understood. 14,15 A large number of evidence places the p53 suppressor gene at a nodal point in the regulation of diverse stress responses. Indeed, a number of cellular stresses including DNA damage, heat shock, hypoxia, hyperoxia, metabolic changes, oncogene activation, and others, converge on p53 protein and cause its activation and stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factors shown to positively regulate p53 transcription include c-myc (Kirch et al, 1999;Lee and Rho, 2000), NF-kB (Pei et al, 1999;Benoit et al, 2000), YY1/NF1 (Lee et al, 1998(Lee et al, , 1999Nayak and Das, 1999), Ap1 (Kirch et al, 1999), and the HoxA5 homeobox containing gene product (Raman et al, 2000). Members of the PAX family are the only mammalian nuclear proteins shown to repress p53 transcription through a binding site present in the ®rst non-coding exon (Stuart et al, 1995).…”
Section: Introductionmentioning
confidence: 99%